The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1017/s0958067099018710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reducing Submandibular Blood Flow on Secretory Responses to Parasympathetic Stimulation in Anaesthetized Cats

Abstract: summary Submandibular secretory responses to stimulation of the parasympathetic chorda-lingual nerve were investigated in five anaesthetized cats before, during and after withdrawal of blood (ca 20 ml kg¢) in order to investigate the consequences of a reduced blood flow through the gland. Stimulation at different frequencies (2, 4, 6 and 8 Hz) evoked a frequency-dependent increase in the flow of submandibular saliva, sodium concentration, electrolyte and protein output. When the blood pressure was reduced (by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…It is unlikely that an increase in de novo synthesis of alpha amylase could account for this boost in sAA levels as there would be insuffi cient time for biosynthesis and secretion of the enzyme. Other authors have reported that increases in salivary protein concentration are associated with dehydration [38] and parasympathetic withdrawal leading to decreased salivary fl ow [14] . Our data from the electrophoretic profi le, which was carried out using samples of similar protein concentrations instead of equivalent volumes, indicates that alterations in TPWS caused by exercise are directly related to alpha-amylase since other salivary proteins were not altered.…”
Section: Discussion ▼mentioning
confidence: 98%
“…It is unlikely that an increase in de novo synthesis of alpha amylase could account for this boost in sAA levels as there would be insuffi cient time for biosynthesis and secretion of the enzyme. Other authors have reported that increases in salivary protein concentration are associated with dehydration [38] and parasympathetic withdrawal leading to decreased salivary fl ow [14] . Our data from the electrophoretic profi le, which was carried out using samples of similar protein concentrations instead of equivalent volumes, indicates that alterations in TPWS caused by exercise are directly related to alpha-amylase since other salivary proteins were not altered.…”
Section: Discussion ▼mentioning
confidence: 98%
“…8 Neuronal control of the submandibular and sublingual glands is provided by parasympathetic fibers of cranial nerve VII via the lingual nerve and submandibular ganglion. [9][10][11] Early studies have suggested transcanal, transtympanic neurectomy of the chorda tympani nerve for the treatment of sialorrhea. 3 The effects of submandibular gland denervation have been well established in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary secretion has been shown to increase during general anesthesia using remifentanil in humans [ 13 ]. In addition, there is a correlation between blood flow to the salivary glands and salivary secretion in anaesthetized cats [ 9 ]. Therefore, it is possible that parotid or other salivary gland tissue blood flow, which was not observed in the present study, had increased.…”
Section: Discussionmentioning
confidence: 99%
“…First, although remifentanil decreases TMBF, MBF and BBF, blood flow to other regions is likely to increase. One report has addressed increased salivary secretion during propofol/remifentanil anesthesia [ 13 ], while another report demonstrated a correlation between blood flow to the salivary glands and salivary secretion [ 9 ]. Accordingly, it is suggested that blood flow to the salivary glands may increase during this type of anesthesia.…”
mentioning
confidence: 99%